Determination of Bot Groups in Social Network Accounts by Multiple Sequence Alignment Method - Sevi, Mehmet; Aydin, Ilhan (Institute of Electrical and Electronics Engineers Inc., 2019)
Social networks have become very important power in our age. The ability of people to meet their needs through social networks has been an important factor in the formation of this power. Many events such as shopping, communication, hobby and research can be done through social networks. Twitter is one of the leading platforms of these social networks. Twitter is a social networking platform that offers a simple but powerful service. Most of the functionality is found in messages with a maximum of 280 characters, in other words in tweets. These tweets mean big data for researchers. An average of 5700 tweets are generated on Twitter per second. There is a lot of important information in this large volume of data. This information can be analyzed and used for many purposes. This information can be used to spread false information such as selection and manipulation of the stock market. In this study we will examine the structure of the accounts that emit this harmful information. © 2019 IEEE.
1st International Informatics and Software Engineering Conference, IISEC 2019 -- 6 November 2019 through 7 November 2019 -- Ankara -- 157111
Keywords: bot; DNA; multiple sequence alignment; social networks; Twitter